Automated cyclers used in peritoneal dialysis: technical aspects for the clinician - Chaudhry RI (Dove Medical Press, 2015)
Rafia I Chaudhry, Thomas A Golper Division of Nephrology and Hypertension, Vanderbilt Center for Kidney Disease, Vanderbilt University Medical Center, Nashville, TN, USA Abstract: Peritoneal dialysis (PD) is a widely accepted and increasingly popular form of dialysis. The invention and technological advancement of the PD cycler further makes PD a convenient option. Prescription-specific parameters are entered into the cycler, which then automatically carries out the steps involved in continuous cycling PD. We review the basics, technical aspects, challenges, and advancements of the cycler. Keywords: peritoneal dialysis, automated peritoneal dialysis, cycler peritoneal dialysis